Takbo! mga pandiwa kapag naging tinig ang tunog - Yambao, Auri Asuncion (Makati City Tahanan Books for Young Readers, 2016)
"Welcome to a world of words where sound makes sense. The Filipino language has many onomatopoeic words, each carrying a sound that describes its meaning."
Keywords: Readers (Primary); Filipino language -- Phonetics